algebra

posted by .

using product rule, power rule, negative rule using scientific notation.

5.4*10^6/2.7*10^4=5.4/2.7*10^6/10^4=2*10^2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Product Rule

    Can someone please help me with this? f(x)=(x-2)^1/2 * (x^2-3)^3 find f'(x) using the product rul. This is what I came up with I just need to know if I did it right. f'(x)=(x-2)^1/2*3(x^2-3)+(x^2-3)^3*(1)^-1/2 Hopefully I did. Thanks.
  2. MoRe HeLp PlEaSe!! (calc)

    Also can I get some help with this LONG, TIRESOME PROBLEM?
  3. math

    Given A = {1, 2, 3, 4} B = {2, 5, 10, 17}, a E A and b E B The mapping rule for f maps 1 to 2, 2 to 5, 3 to 10 and 4 to 17. (A) Write the mapping rule in the format of the listing method. Display the mapping using the listing format. …
  4. math

    Given A = {1, 2, 3, 4} B = {2, 5, 10, 17}, a E A and b E B The mapping rule for f maps 1 to 2, 2 to 5, 3 to 10 and 4 to 17 (b) Write the mapping rule in the format of the listing method. Display the mapping using the listing format. …
  5. Calculus

    How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?
  6. MATH

    IF MY FRIEND CHOOSE A NUMBER AND THEN USED A RULE TO MAKE A NEW NUMBER HE DID THIS 7 TIMES USING THE SAME RULE THE TABLE BELOW SHOWS HIS RESULTS WHAT RULE COULD HAROLD HAD USED EXPLAIN INPUT OUTPUT 28 6 12 3 9 10 16
  7. Calculus

    Match the rule with the title: ____ 3. d/dx [f(x)/g(x) ]=(g(x) f^' (x)-f(x) g^' (x))/[g(x)]^2 ____ 4. d/dx [f(g(x))]=f^' (g(x))∙g'(x) ____ 5. d/dx [f(x)∙g(x)]= f(x) g^' (x)+g(x) f^' (x) ____ 6.d/dx [x]=1 ____ 7. d/dx [f(x)+g(x)]= …
  8. Math (Calculus)

    Hello, Could somebody please help me with the following question?
  9. Math (Expanding logarithms)

    Use the properties of logarithms to expand this functiion?
  10. Math (Integrals)

    Find the indefinite integral in two ways. ∫(2x-1)^2 dx The first way I used was using the power rule and chain rule with substitution. Let u = 2x - 1 du = 2 dx (1/2)∫ u^2 du (Applying power rule) (1/2) * (u^3/3) + C =(2x-1)^3/6 …

More Similar Questions